STRENGTHENING LOCAL ECONOMY THROUGH COMMUNITY-BASED TOURISM IN GOVERNANCE PERSPECTIVE (Study at Sidomulyo Tourism Village, Batu City) - Rifka Aulya; Lely Indah Mindarti; Fadillah Amin (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2016)
Tourism has an important role to create and expand the employment opportunities, promote development and increase the district own source revenue, enrich local culture, and preserve the environment. Batu City is one of famous tourism destinations in Indonesia which has a high potential in natural and agricultural tourism attraction. The tourism development in Sidomulyo Tourism Village emphasizes on community empowerment. One of the problems that still faced by its people is the capital limitation, inadequate facilities, lack of human resources and technology. Therefore, the implementation of tourism village should be based on community based tourism that emphasizes self-reliance and community empowerment. Community-Based Tourism (CBT) implementation has the purpose to develop tourism industry; promote rural tourism based on local community empowerment; create jobs; reduce poverty; build an independent and resilient society; create an innovative human; and improve cross-sector cooperation in the tourism village development. Implementation of CBT in Sidomulyo couldn’t be separated from the role of the various stakeholders. It is accordance with the principles of governance that the implementation of development which involving all actors namely the state (government), private sector, and society. The process in realizing the independent community through community empowerment program of tourism with the concept of community based tourism may be optimized for their several contributing factors. Some things become a supporting factor due to give a positive contribution to the implementation of community-based tourism. Keywords: Local Development, Tourism, Governance, Batu City, Indonesia.